The site reliability workbook practical ways to implement SRE - Beyer, Betsy; Murphy, Niall Richard; Rensin, David K.; Kawahara, Kent; Thorne, Stephen (O'Reilly Media, 2018)
An expansion on the understanding of Google SRE, providing 'worked examples' for each essential facet of this area of IT prepared in co-operation with Google cloud customers based on their experiences. Instructs on methodology for running services at scale and starting SRE in greenfield or brownfield fashion.
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed August 1, 2018)
Keywords: Information technology -- Management; Reliability (Engineering); Computer engineering; Technologie de l'information; Gestion; Fiabilité; Ordinateurs; Conception et construction; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Information technology; Management